(untitled) (Journal of Rashid Latif Medical College, 2022)
Objective: Vigna mungo (mash) is a widely consumed legume in Pakistanand also used globally. This study was carried out for detailedcharacterization of oils from mash seeds from four indigenously cultivatedvarieties, as very little information is available on the oil composition of mash seeds and inter-varietal variation in oil composition. Materials andMethods: Morphological study was done for each cultivar prior to extraction and characterization of mash seed oil by conventional methods. Seed volume, seed density, hydration capacity, hydration index, swelling capacity, swelling index was determined for mash seeds of each of four cultivars. Oil extraction was done by soxhlet apparatus and characterization of oil for different ingredients was done using GC-MS and HPLC. Results: The oil content was relatively low (1–2%). The investigated physiochemical parameters included refractive indices (RI) at 40 C (1.6–1.9), relative density (1), iodine value (IV) (114.3 –117.1), saponification value (SV) (156.0–167.4 mg KOH/g) and unsaponifiable matter (UM) (14.3-15.3%). Tocopherol contents were also determined and each cultivar was found to contain appreciable amounts of these constituents (Table 4).The concentration of ãtocopherols were found to be greater than the δ-and á-tocopherol which is quite different than mungbean.. Bulk chemical properties such as acid value (AV), saponification value (SV), iodine value (IV), PV, and p-anisidine value (pAV) give structural, stability, and quality information about oils and fats. The UM ranged from 14.3 to 15.3 (Table 2) and it was revealed that cultivars differed significantly with respect to UM. These values are in consistent with the UM pattern observed for low oil-bearing seeds. Conclusion: The findings of the study showed that mash [Vigna mungo(L.) Happer], is a potentially valuable legume crop with considerable nutritional quality oil among all the cultivars.